Pedagogy and practice in STEM field experiences: intersections of student and mentor identity and impacts upon student outcomes. Issue 4 (8th August 2018) - Felege, Christopher J.; Hunter, Cheryl; Hunter, Joshua; Ellis-Felege, Susan N.
ABSTRACT: Practicums, internships and field experiences are essential components in many fields. These varied experiences embed both students and their mentors in immersive experiences. Such immersive experiences are essential for STEM students preparing for future jobs, yet little is known about how these research-intensive and immersive experiences impact the practice of teaching in the natural sciences. In order to evaluate the impact, opportunities and challenges associated with such experiences, our team collected and analysed end-of-semester reflections from five students and their faculty mentor. Thematic analysis related to inferences and implications about the impacts of the experience showed a need to formalize and further develop an understanding of both students' self-identity and the cultural attitudes of the students and the mentor.